Terbium (III) coordination polymer–copper (II) compound as fluorescent probe for time‐resolved fluorescence 'turn‐on' detection of hydrogen sulfide. (29th August 2017) - Chen, Lili; Tan, Hongliang; Xu, Fugang; Wang, Li
Abstract: With recognition of the biological importance of hydrogen sulfide (H2 S), we present a simple and effective fluorescent probe for H2 S using a Tb 3+ coordination polymer–Cu 2+ compound (DPA/Tb/G–Cu 2+ ). Dipicolinic acid (DPA) and guanosine (G) can coordinate with Tb 3+ to form a macromolecular coordination polymer (DPA/Tb/G). DPA/Tb/G specifically binds to Cu 2+ in the presence of coexisting cations, and obvious fluorescence quenching is observed. The quenched fluorescence can be exclusively recovered upon the addition of sulfide, which is measured in the mode of time‐resolved fluorescence. The fluorescence intensities of the DPA/Tb/G–Cu 2+ compound enhance linearly with increasing sulfide concentrations from 1 to 30 μM. The detection limit for sulfide in aqueous solution is estimated to be 0.3 μM (at 3σ). The DPA/Tb/G–Cu 2+ compound was successfully applied to sense H2 S in human serum samples and exhibited a satisfactory result. It displays some desirable properties, such as fast detection procedure, high selectivity and excellent sensitivity. This method is very promising to be utilized for practical detection of H2 S in biological and environmental samples.